2021
DOI: 10.3389/fendo.2021.628169
|View full text |Cite
|
Sign up to set email alerts
|

Effect of LHCGR Gene Polymorphism (rs2293275) on LH Supplementation Protocol Outcomes in Second IVF Cycles: A Retrospective Study

Abstract: Infertility is a major concern for couples wanting to have progeny. Despite recent advances in the field of IVF, success rates still need improvement. Understanding the patient’s variability and addressing it with personalized interventions may improve the success rate of fertilization and live births. This study examined the impact of a personalized pharmacogenomic approach on LH supplementation on the pregnancy and live birth rate outcomes in comparison with the traditional approaches. 193 patients undergoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Moreover, in the same study, the pregnancy rate was significantly higher in serine carriers who received rFSH/rLH than in those receiving rFSH alone ( 64 ). These data combined with others ( 65 ) suggests a probable benefit of administering LH supplementation to women undergoing IVF on the basis of their single-nucleotide polymorphism profile (rs2293275) of LHCGR.…”
Section: Genetic Variants In Gonadotropins’ Receptors: Pharmacologica...mentioning
confidence: 57%
“…Moreover, in the same study, the pregnancy rate was significantly higher in serine carriers who received rFSH/rLH than in those receiving rFSH alone ( 64 ). These data combined with others ( 65 ) suggests a probable benefit of administering LH supplementation to women undergoing IVF on the basis of their single-nucleotide polymorphism profile (rs2293275) of LHCGR.…”
Section: Genetic Variants In Gonadotropins’ Receptors: Pharmacologica...mentioning
confidence: 57%
“…As already stated in this Delphi consensus, there are limited data on the influence of polymorphisms of the LHB/LHCGR genes on ovarian stimulation outcomes and their usefulness in pharmacogenomic research in ART. While the usefulness of polymorphisms in these genes per se remains to be determined, a recent study (also published since the selection of the literature for consideration in this Delphi Consensus) may indicate some clinical value in determining the need for LH supplementation compared with current supplementation protocols, reporting higher clinical pregnancy rates (p=0.049) and a trend towards improved live birth rates (p=0.082) in 193 women when supplementation was based on a woman's SNP profile compared with conventional methods (76). Furthermore, in a cross-sectional study of LHCGR rs2293275 (c.935 A>G, p.Asn312Ser), Lindgren et al reported no significant difference in the number of oocytes retrieved or obvious differences in embryo quality between Ser/Ser, Asn/Ser or Asn/ Asn carriers.…”
Section: Discussionmentioning
confidence: 99%
“…Literature demonstrates the correlation of LHCGR genotype with PCOS, slow response to ovarian stimulation along with relation to FSH consumption and dose of LH required. [ 23 24 25 ] Interestingly, 82% of the patient group had AA genotype which indicates that it could be a strong biomarker for female infertility.…”
Section: Discussionmentioning
confidence: 99%